Characterization and manufacturing technology of cellulose nano-biochar as natural feedstocks for advanced carbon materials in soil remediation - Syahida Farhan A.; Abu Bakar N.F.; Idris S.S.; Kadri A.; Abd Rahman N.; Ismail S.N.; Osman M.S.; Naim M.N. (Elsevier, 2025)
There is a growing interest in a diverse array of nano-biochar derived from cellulose-based feedstocks to address the most pressing ecosystem challenges nowadays. Cellulose has emerged as the primary material for the production of nano bio charcoal with distinctive ability of low-cost, abundant in nature, renewable, sustainable, and biocompatible properties. Thus, cellulose-based nanomaterials attracted the attention of the research community due to their broad-spectrum applications in the fields of agriculture, environment, catalysis, energy, and biomedical. Soil contamination by heavy metals, pesticides, herbicides, and polycyclic aromatic hydrocarbons is also regarded as one of the serious issues that implement the treatment by nano-biochar. As a result, soil remediation has been achieved through the improvement of soil fertility, enhancement of plant productivity and yield, increase in soil quality for plant growth and development, and promote carbon sequestration. Overall, this review chapter has evaluated and presented the preparation, characterization, and manufacturing technology of cellulose nano bio charcoal as natural feedstock for advanced carbon material, especially in soil remediation studies. ? 2025 Elsevier Ltd. All rights reserved.